Relationship between Microstructure and Properties of 1380 MPa Grade Bainitic Rail Steel Treated by Online Bainite-Based Quenching and Partitioning Concept - Miao Liu; Yusong Fan; Xiaolu Gui; Jie Hu; Xi Wang; Guhui Gao (Metals, 2022)
According to the concept of the bainite-based quenching and partitioning (BQ&P) process, we designed the online heat treatment routes of bainitic rail steel for heavy haul railway. The new heat treatment process reduced the fraction and size of the blocky martensite/austenite (M/A) islands formed during the conventional air-cooling process. The M/A islands are coarse and undesirable for mechanical properties. A new kind of 1380 MPa grade bainitic rail steel with more uniform microstructure and better mechanical properties was produced by the online BQ&P process. We characterized the multiphase microstructures containing bainite, martensite, and retained austenite of 1380 MPa grade bainitic rail steels via optical microscope, scanning electron microscopy, transmission electron microscopy, and X-ray diffractometer. We investigated in-depth the relationship between the microstructure, retained austenite stability, and mechanical properties, particularly the resistance to wear and rolling contact fatigue, of the new 1380 MPa grade bainitic rail steels. Meanwhile, the conventional air-cooling bainitic rail steel was studied as a comparison.